"Someone will take care of it". Households' understanding of their responsibility to prepare for and cope with electricity and ICT infrastructure breakdowns. (September 2020) - Heidenstrøm, Nina; Throne-Holst, Harald
Abstract: Extensive infrastructure breakdowns are likely to become more frequent in the future as a result of continually complex and interconnected infrastructures vulnerable to weather and climate changes as well as intended attacks. By means of ethnographic interviews with households in Norway, this article examines their engagement in preparing for and coping with such breakdowns. It focusses on the division of responsibility between households, the authorities, and industry actors, and demonstrates that households do not believe they are responsible for preparedness, saw little advantage in contacting the authorities or industry actors, and chose to wait until someone handled the outage. However seemingly unprepared, households mobilised their social networks, used skills from previous experiences, local knowledge on infrastructure and weather, and material resources. Despite low engagement in the preparedness measures suggested by the authorities, we propose households to be considered key actors in societal preparedness by calling for greater attention to the socially shared practices households engage in that are not explicit preparedness actions, and for crisis management policies in the energy sector to provide the vehicles to mobilise household resources. Highlights: Households show low engagement in preparedness for infrastructure breakdowns. Households see authorities and grid companies as responsible for managing breakdowns. However, households mobilised informal preparedness resources to cope with breakdowns. These resources need to be recognised by risk management policy in the energy sector. Households should be involved in developing local preparedness plans.